A single PCR-sequencing method to establish the frequency of kdr alleles in the stable fly, Stomoxys calcitrans: application to seven livestock farms from south of France - Mariana Ribeiro Sato; Géraldine Bossard; Guilhem Sempere; Philippe Jacquiet; Christelle Grisez; Geoffrey Gimonneau; Marc Desquesnes (PLoS ONE, 2025)
The stable fly, Stomoxys calcitrans, is a cosmopolite pest causing direct and indirect nuisances on livestock, due to painful bite, harassment, blood despoliation and biological or mechanical transmission of viruses, bacteria and parasites. Its control is mainly based on direct applications of pyrethroid insecticides on livestock, although evidences show limited efficiency due to short term effects and high levels of phenotypic and genotypic resistance. Diagnosis of genetic resistance is currently based on a series of point mutation PCRs showing limitations. Based on fly specimens trapped in southern France, this study aims to establish a new diagnosis method to investigate kdr allele frequencies in livestock farms. A total of 144 S. calcitrans specimens were collected from seven farms (1 with insecticide usage, and 6 without) and processed individually through a single PCR using newly designed primers amplifying a 340 bp fragment including the mutation site of the voltage-sensitive sodium channel domain II; PCR products were then sequenced. Among the 104 individuals successfully sequenced, the methodology allowed to detect the wild-type, kdr-his and kdr genotypes encoding for leucine, histidine and phenylalanine, respectively. Although the wild-type was the most prevalent, resistance alleles were detected in all farms, especially at the veterinary school, where insecticides are commonly used. These results highlight that genotypic insecticide resistance in S. calcitrans populations is widespread. This single PCR-sequencing method, simple, cost-effective and reliable, will allow determining prevalence, distribution and resilience of genotypic pyrethroid insecticide resistance, a primary data to support a conversion from chemical vector control toward environmental-friendly strategies.